Effect of Types of Cayenne Pepper and Chitosan Concentration of Shrimp Shell Waste as Biocoating to Extend Shelf Life - Roisatul Chumaidah; Meutia Maulina; Lulu Nurliyantini; Trisna Juliati; Nur Arifah Qurota A’yunin; Septian Cahya Azhari (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
This study aims to determine the effect of chitosan concentration on types of cayenne pepper and the interaction between the two as a respiration barrier during storage at room temperature. The research was conducted at the Basic Laboratory of the Faculty of Agriculture, Siliwangi University from June to August 2021. This research method used a Completely Randomized Factorial Design (CRD) consisting of two factors, repeated four times. The first factor was the type of cayenne pepper (A), namely green cayenne pepper (A1) and red cayenne pepper (A2), the second factor was the concentration of chitosan (C), namely 0% chitosan (C1), 1% chitosan (C2) and 2% chitosan (C3). The research data were analyzed using variance and further tested with Duncan's multiple range test with a significance level of 5%. The results showed that there was an interaction between the type of cayenne pepper and the concentration of chitosan on vitamin C content, phenolic content, and fruit weight loss of cayenne pepper.